REVIEW OF: GOLUBKOVA O.N. FUNDAMENTALS OF SCIENTIFIC RESEARCH IN THE PROFESSIONAL FIELD: TEXTBOOK - A.A. Bilyalova; A.N. Utekhina (Многоязычие в образовательном пространстве)
This review examines the contents of an electronic textbook ‘Fundamentals of Scientific Research in the Professional Field’ by O.N. Golubkova, Candidate of Pedagogy, Associate Professor. The textbook effectively presents the materials needed for studying the ‘Methodology of Scientific Research’ discipline in a clear and engaging didactic form. This publication is aimed at students pursuing Master’s degrees in translation studies, but it will also benefit learners in other language-related fields. The textbook serves as a valuable resource for preparing for lectures and practical sessions, as well as for independent study. The research methodology course enhances students’ research skills and intensifies their final qualifying paper writing by deepening their understanding of methodological principles. The textbook covers three key areas: the methodological components of a thesis, the design and execution of research, and the refinement of research discourse. The textbook explores the principles of selecting information and characterises the content of its methodological components, including the introduction, theoretical and empirical sections of a thesis as well as outcomes and conclusions. It analyses research methods and emphasises the importance of a systematic approach in exploring the materials. Significant focus is given to designing the theoretical and empirical sections of the study, outlining the stages of developing a theoretical concept and examining the functions and characteristics of theoretical knowledge. An algorithm for describing text fragments comparing the original and translation is discussed, and principles for working with empirical material and approaches to structuring the relationship between theoretical and practical chapters are analysed. The discourse of written scientific communication is enhanced by studying the linguistic features of scientific writing and the diversity of its genres. Patterns in the use of methodological concepts based on their functions in a study are highlighted. The textbook is organised into ten chapters presented in a didactic sequence, each accompanied by control questions to assess understanding. Visual aids such as tables, diagrams, and drawings are used extensively to improve the clarity and effectiveness of the material. The theoretical value of the textbook lies in its systematic presentation of methodological categories and concepts, providing students with essential research tools. Practically, it enhances translation skills, particularly for master’s thesis writing, and equips students with knowledge applicable in their future careers as skilled translators.